ФОРМИРОВАНИЕ ЭКСПЕРИМЕНТАЛЬНЫХ НАВЫКОВ УЧАЩИХСЯ НА ОСНОВЕ ПРОБЛЕМНОГО ОБУЧЕНИЯ - Бектурганова, З.К.; Ерекеева, А.С. (SCIENCE and SOCIETY, 2022)
The article discusses research on problem-based learning, the main trends in changing interest in the methodology of teaching chemistry to the formation of experimental skills based on problem-based learning.
Keywords: intensive renewal; deep development of social values; multifaceted development of the student; theoretical and current research methods